Парадигма міжнародних відносин у добу Нового часу (концепція Пола Кеннеді) // Актуальні питання суспільних наук та історії медицини. - Sych, Alexandr (My University, 2021)
The article considers the concept of international relations proposed 30 years ago by the famous historian and political analyst Paul Kennedy. The author of the article tried to find out how relevant its key provisions are for understanding both the history and the current state of international relations.